2020
DOI: 10.22541/au.159985895.51837688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ebselen reduces cigarette smoke-induced vascular endothelial dysfunction in mice

Abstract: Background and Purpose: It is well established that both smokers and patients with COPD are at a significantly heightened risk of cardiovascular disease (CVD), although the mechanisms underpinning the onset and progression of comorbid CVD are largely unknown. Here, we explored whether cigarette smoke (CS) exposure impairs vascular function in mice and given the well-known pathological role for oxidative stress in COPD, whether the antioxidant compound ebselen prevents CS-induced vascular dysfunction in mice. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Smoking cessation restores body weight and reduces BALF cellularity Similar to previously reported, CS exposure caused a suppression of weight gain when compared to sham mice [7,32,33]. Upon cessation, the body weight of the mice rapidly re-bounced and were no different to that of sham-treated at 18 Cessation gradually alters the pulmonary in ammatory pro le.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Smoking cessation restores body weight and reduces BALF cellularity Similar to previously reported, CS exposure caused a suppression of weight gain when compared to sham mice [7,32,33]. Upon cessation, the body weight of the mice rapidly re-bounced and were no different to that of sham-treated at 18 Cessation gradually alters the pulmonary in ammatory pro le.…”
Section: Resultssupporting
confidence: 83%
“…The hippocampus is highly susceptible to oxidative insults [72], thus, it seems highly plausible that ebselen may be able to reduce the CS-induced oxidative burden globally, however, hippocampal oxidative stress may remain elevated alongside the elevated microglial pro le. This is not unprecedented given that the attenuation of pulmonary in ammation following ebselen administration is largely due to a reduction in neutrophilic in ltration [7,10], leading us to postulate that ebselen's memory enhancing ability may be exerted via a microglial-independent mechanism which targets synaptic integrity in smokers. Synapses are formed by the functional contact of presynaptic axonal terminals with postsynaptic dendritic processes allowing for the e cient transmission of signal [73,74].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although yet to be fully established, the "spill-over" of local lung inflammation in COPD has been demonstrated to drive CVD risk (Barnes, 2019). In a preclinical model of COPD, Brassington et al (Brassington et al, 2021) demonstrated that oxidative stress from CS exposure may cause inflammatory cell infiltration into the vascular wall and endothelial dysfunction, suggesting oxidative stress may be a missing link. In addition to marking the imbalance between reactive oxygen species (ROS) and endogenous antioxidant defence, oxidative stress may simultaneously exacerbate comorbidities, stimulating fibrosis and emphysema development of the lungs by amplifying chronic inflammation (Barnes, 2020).…”
Section: Introductionmentioning
confidence: 99%